Evolutionary conservation of the spliceosomal protein, U2B''. - Simpson, G G (1991)
U1 and U2snRNPs play key roles in pre-mRNA splicing. The interactions between the U1 and U2snRNP-specific proteins, U1A, U2A' and U2B'' and their respective UsnRNAs are of interest both to elucidate their roles in splicing, and as models to study RNA-protein interactions. We have cloned a full-length cDNA, encoding U2B'', from potato. This is the first report of a sequence for a plant UsnRNP protein. The plant U2B'' sequence exhibits extensive similarity with the human U2B'' protein at both the DNA and amino acid levels. The evolutionary conservation at the protein level, particularly in sequences implicated in determining specific binding to U2snRNA, suggests conservation of U2B'' function from plants to man. The significance of amino acid substitutions in the RNP-80 motif with respect to U2snRNA binding in plants is discussed.